Fixed Traffic and Intersection Simulation in Front of UTHM Pagoh - Goo , Jun Hong; Seah , Xiang Feng; Adnan, Faiz Fahmi; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2025)
In Malaysia, traffic congestion is a common problem that often occur during rush hours that leading to adverse social, economic, and environmental issues. Edu Hub Pagoh, the place which boasts four esteemed educational institutions UTHM, UTM, Politeknik Tun Syed Nassir and UIA is also not spared from experiencing traffic congestion which might happen due to high traffic volume along the road itself especially at Persiaran Sarjana (In front of UTHM Pagoh main gate). Therefore, this study was conducted to determine the speed and traffic volume at the Persiaran Sarjana at Pagoh town in working days and non-working days, to develop traffic simulation of the case study location using PTV-VISSIM students’ version 2023 to analyse the Level of Service (LOS) to reduce or control the congestion issues at the Persiaran Sarjana during the peak hour in the morning, afternoon and evening. After conducting the experiment, this study has collected all the data for optimization. The LOS of Persiaran Sarjana in working days is LOS D and non-working days is LOS B. This finding could greatly contribute to future traffic studies.